Long-term Exposure to Air Pollution and Markers of Inflammation, Coagulation, and Endothelial Activation: A Repeat-measures Analysis in the Multi-Ethnic Study of Atherosclerosis (MESA) - Hajat, Anjum (Epidemiology, 2015)
BACKGROUND: Air pollution is associated with cardiovascular disease, and systemic inflammation may mediate this effect. We assessed associations between long- and short-term concentrations of air pollution and markers of inflammation, coagulation, and endothelial activation. METHODS: We studied participants from the Multi-Ethnic Study of Atherosclerosis from 2000 to 2012 with repeat measures of serum C-reactive protein (CRP), interleukin-6 (IL-6), fibrinogen, D-dimer, soluble E-selectin, and soluble Intercellular Adhesion Molecule-1. Annual average concentrations of ambient fine particulate matter (PM(2.5)), individual-level ambient PM(2.5) (integrating indoor concentrations and time–location data), oxides of nitrogen (NO(x)), nitrogen dioxide (NO(2)), and black carbon were evaluated. Short-term concentrations of PM(2.5) reflected the day of blood draw, day prior, and averages of prior 2-, 3-, 4-, and 5-day periods. Random-effects models were used for long-term exposures and fixed effects for short-term exposures. The sample size was between 9,000 and 10,000 observations for CRP, IL-6, fibrinogen, and D-dimer; approximately 2,100 for E-selectin; and 3,300 for soluble Intercellular Adhesion Molecule-1. RESULTS: After controlling for confounders, 5 µg/m(3) increase in long-term ambient PM(2.5) was associated with 6% higher IL-6 (95% confidence interval = 2%, 9%), and 40 parts per billion increase in long-term NO(x) was associated with 7% (95% confidence interval = 2%, 13%) higher level of D-dimer. PM(2.5) measured at day of blood draw was associated with CRP, fibrinogen, and E-selectin. There were no other positive associations between blood markers and short- or long-term air pollution. CONCLUSIONS: These data are consistent with the hypothesis that long-term exposure to air pollution is related to some markers of inflammation and fibrinolysis.